Chromosome Stability of Synthetic-Natural Wheat Hybrids - Zhao, Laibin; Xie, Die; Fan, Chaolan; Zhang, Shujie; Huang, Lei; Ning, Shunzong; Jiang, Bo; Zhang, Lianquan; Yuan, Zhongwei; Liu, Dengcai; Hao, Ming (Frontiers in Plant Science, 2021)
Primary allopolyploids are not only ideal materials to study species evolution, but also important bridges in incorporating genetic diversity of wild species into crops. Primary allopolyploids typically exhibit chromosome instability that a disadvantage trait in crop breeding. Newly synthesized hexaploid wheat has been widely used in wheat genetics and breeding studies. To better understand the cytological and genetic basis of chromosome instability, this study investigated the chromosomes of a large number of seeds derived from the synthetic wheat SHW-L1 and its hybrids with natural wheat. SHW-L1 exhibited persistent chromosome instability since we observed a high frequent chromosome variation de novo generated from euploid SHW-L1 plants at the 14th generation of selfing (F14). High frequent chromosome variations were also observed in the F2 hybrids and most of the analyzed recombinant inbred lines (RILs) at F14, derived from the cross of SHW-L1 with common wheat variety Chuanmai 32. Chromosome instability was associated with frequent univalency during meiotic metaphase I. The experiment on reciprocal crosses between SHW-L1 and Chuanmai 32 indicated that cytoplasm has not obvious effects on chromosome instability. An analysis on 48 F14 RILs revealed chromosome variation frequency was not associated with the Ph1 alleles from either SHW-L1 or Chuanmai 32, rejecting the hypothesis that chromosome instability was due to the Ph1 role of synthetic wheat. In the analyzed RILs, chromosome instability influences the phenotype uniformity, showing as obvious trait differences among plants within a RIL. However, the analyzed commercial varieties only containing ~12.5% genomic components of synthetic wheat were chromosomally stable, indicating that chromosome instability caused by synthetic wheat can be effectively overcome by increasing the genetic background of common wheat.